The Other Side of the RAAS: Aldosterone Improves Migration of Cardiac Progenitor Cells. Issue 11 (November 2015) - Könemann, Stephanie; Wenzel, Kristin; Ameling, Sabine; Grube, Karina; Hammer, Elke; Könemann, Raik; Samal, Rasmita; Völker, Uwe; Felix, Stephan B.
<x xml:space="preserve">Abstract</x> Stem cell therapy is a promising new option for patients suffering from heart failure. Though many clinical studies show encouraging results, little is known about the signals which cause stem cells to home to diseased but not to healthy hearts. We hypothesized that aldosterone as one of the main players of heart failure functions as an attractant for progenitor cells and stimulates their migration. Stem cell antigen‐1 (Sca‐1) positive cells were isolated from the hearts of wild type FVB mice via magnetic cell sorting. The migration rate of the cells was determined using aldosterone as an attractant in a modified Boyden chamber (n = 5). Aldosterone led to a dose dependent increase in migration rate and this effect could be prevented by adding its blocker eplerenone. The mineralocorticoid receptor could be detected on Sca‐1+ cells via western blot and immunofluorescence. Therefore, aldosterone seems to play a role in stem cell migration and there the effect is most likely mediated by the mineralocorticoid receptor. J. Cell. Physiol. 9999: 2829–2836, 2015. © 2015 Wiley Periodicals, Inc.